2023
DOI: 10.1007/s11101-023-09853-4
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactones: diversity, perception, and hydrolysis

Abstract: Strigolactones (SLs) are a unique and novel class of phytohormones that regulate numerous processes of growth and development in plants. Besides their endogenous functions as hormones, SLs are exuded by plant roots to stimulate critical interactions with symbiotic fungi but can also be exploited by parasitic plants to trigger their seed germination. In the past decade, since their discovery as phytohormones, rapid progress has been made in understanding the SL biosynthesis and signaling pathway. Of particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 122 publications
(231 reference statements)
0
4
0
Order By: Relevance
“…S17, C to F). Several of these residues were previously found to not only coordinate other synthetic ligands like GR24 but also help differentiate ligand sensitivity (34)(35)(36)(37). These structurally altered sequences (shown in boxes) were located near the N-and C-terminal regions of PhKAI2ia and found to coincide with the potential binding sites of (−)-germacrene D that were determined by the simulation results (fig.…”
Section: Phkai2ia Stereospecifically Perceives (−)-Germacrene Dmentioning
confidence: 63%
“…S17, C to F). Several of these residues were previously found to not only coordinate other synthetic ligands like GR24 but also help differentiate ligand sensitivity (34)(35)(36)(37). These structurally altered sequences (shown in boxes) were located near the N-and C-terminal regions of PhKAI2ia and found to coincide with the potential binding sites of (−)-germacrene D that were determined by the simulation results (fig.…”
Section: Phkai2ia Stereospecifically Perceives (−)-Germacrene Dmentioning
confidence: 63%
“…Residue A191 has been previously reported to be a divergent residue in other species but is an alanine at that position in the majority of species assessed including in grasses. Previous studies have demonstrated how amino acid substitutions in the ligand binding pocket can influence receptor function by altering specificity and efficacy towards different ligands (37, 40, 49, 50). Strikingly, due to its distinct proximity to the ligand binding pocket, residue C162 was selected for further inspection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The SL multifaceted roles, as endo-and exo-signals, are related to the presence of C (open or closed) and D rings, connected via an enol ether bridge. This part of the SLs (canonical or non-canonical) bind to similar receptors from the (super)family of α/β hydrolase fold proteins and trigger the cascade reactions that determine the specific response to SLs in different organisms [36].…”
Section: Introductionmentioning
confidence: 99%